Functional Broth - Peterson, Don (Petits Propos Culinaires, 2017)
The author explores the synergies between slow cooked broths and dry-aged or wet-aged ferments. Examples include borscht, Korean haejangguk and Japanese misoshiru. The synergy produces unami.